The Role of Notaries in Making Deeds of Changes to Land Rights That Have Not Been Certified - Pertiwi, Rohmatika Puspita Husadawati (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This research aims to find out the role of Notaries and PPATs in certifying land rights that have not been certified, also to find out the value of legal certainty of land rights that have not been certified, and to find out how the legal status of changes to land rights that have not been certified is. The research approach method used is normative law, namely a type of approach that refers more to the type of legislative approach, The Statute Approach. The types and sources of data that researchers use, namely secondary data, are divided into primary legal, secondary legal and tertiary legal materials. The data collection method uses library research and interviews and the data analysis method uses qualitative methods. The research results show that Notaries and PPATs must play a role in certifying land rights so that the rights and obligations of the certificate are clear and to avoid disputes. Apart from that, the PPAT Notary also plays a role in making deeds, if there are rights to land that have not been certified. A deed is made as proof that the right to the land has been certified, and if the land is to be bought and sold then the land title is valid because a certificate has been made. Uncertified land rights guarantee